(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Daily wage workers and major contracts are implemented daily in the MSME sector. Most employees maintain their bank accounts at the place of work. Therefore, the MSME sector and employees were significantly affected. Since the onset of the financial crisis, the MSME s sector is struggling to achieve healthy growth rates and revive the economy. Demonetization was widely implemented to bring transparency and accountability to the people in the political and economic system. Due to demonetization and mis-planning action, some MSMEs closed down their units as sales fell and they faced loss of funds. The three factors namely shortage of money, short term inflation and financial problems show a problems of MSME. The analysis highlighted that male authorities highly rated towards problems of MSME than female authorities. It is found that there is influence of Demonetization on Problems of MSME. For this, the Government should take efforts to create awareness about digitization and provide appropriate cultivation to MSME authorities and their employees to use it.